PROS1 shapes the immune-suppressive tumor microenvironment and predicts poor prognosis in glioma - Wang, Jinxiang; Wu, Nisha; Feng, Xiaowei; Liang, Yanling; Huang, Meijin; Li, Wenle; Hou, Lingmi; Yin, Chengliang (Frontiers in Immunology, 2023)
Background: Glioma is the most malignant cancer in the brain. As a major vitamin-K-dependent protein in the central nervous system, PROS1 not only plays a vital role in blood coagulation, and some studies have found that it was associated with tumor immune infiltration. However, the prognostic significance of PROS1 in glioma and the underlying mechanism of PROS1 in shaping the tumor immune microenvironment (TIME) remains unclear. Results: The level of PROS1 expression was significantly increased in glioma in comparison to normal tissue, which was further certificated by qRT-PCR and WB in LN-229 and U-87MG glioma cells. High expression of PROS1 positively correlated with inflammation, EMT, and invasion identified by CancerSEA, which was also proved by the downregulation of PROS1 could suppress cells cell migration, and proliferation in LN-229 and U-87MG glioma cells. GO and KEGG analysis suggested that PROS1 was involved in disease of immune system and T cell antigen receptor pathway. Immune cell infiltration analysis showed that expression of PROS1 was negatively associated with pDC and NK CD56 bright cells while positively correlated with Macrophages, Neutrophils in glioma. Immune and stromal scores analysis indicated that PROS1 was positively associated with the immune score. The high level of PROS1 resulted in an immune suppressive TIME via the recruitment of immunosuppressive molecules. In addition, Increased expression of PROS1 was correlated with T-cell exhaustion, M2 polarization, and poor Overall-Survival (OS) in glioma. And it was significantly related to tumor histological level, age, and primary therapy outcome. The results of our experiments and various bioinformatics approaches validated that PROS1 was a valuable poor prognostic marker. Conclusion: Increased expression of PROS1 was correlated with malignant phenotype and associated with poor prognosis in glioma. Besides, PROS1 could be a possible biomarker and potential immunotherapeutic target through promoting the glioma immunosuppressive microenvironment and inducing tumor-associated macrophages M2 polarization. Keywords: PROS1, exhausted T cell, biomarker, glioma immunosuppressive microenvironment, prognosis